Penggunaan Rubu’ Mujayyab untuk Meningkatkan Pemahaman Konsep Matematis Siswa - Ramadhan, Muhammad Rizky; Hakim, Wildan (FKIP Universitas Mataram, 2025)
Mathematic learning is often perceived as abstract and difficult by students due to the lack of visualization of angle concepts and mathematic functions. The rubu' mujayyab, a historical tool from Islamic science, offers cultural connections that can increase student motivation and engagement in understanding modern mathematic concepts. Recent studies have shown that the rubu' mujayyab is effective in helping students understand the concepts of intelligence and trigonometry significantly, as well as improving mathematical representation skills and learning motivation. One of the challenges in implementation is the availability and skills of teachers in its use. However, simple training can help teachers read scales and interpret angle values mathematically. These findings strengthen the argument that the rubu' mujayyab is not only historical but also relevant for contemporary education, transforming it into a viable alternative learning medium in mathematics courses